Low Voltage Rf Microelectro-Mechanical Switch Using 0.35 μm MIMOS CMOS Compatible Process - Jaafar, Haslina (2014)

(untitled)
Low voltage RF MEMS switch that can be integrated with other circuits is required in the consumer product, industrial and telecommunication sector. Voltage actuation less than 10 V with simple fabrication process is desirable as most of applications need low power system with low fabrication cost. Suis RF MEMS bervoltan rendah dan boleh berintegrasi dengan litar lain sangat diperlukan di dalam produk pengguna, sektor industri dan telekomunikasi. Voltan penggerak kurang daripada 10 V dengan proses fabrikasi yang mudah sangat dikehendaki kerana kebanyakan aplikasi memerlukan sistem kuasa rendah dengan kos fabrikasi yang rendah.